Reimagining life : philosophical pessimism and the revolution of surrealism - Kadri, Raihan, 1977- (Fairleigh Dickinson University Press ; Rowman & Littlefield Pub. Group, 2011)
The innovative, wide-ranging study deftly traverses fields of art, politics, philosophy, psychology, and literature. Reimagining Life redefines Surrealism's place in modern intellectual history and offers a new vision of how Surrealist discourse can be connected to contemporary debates in cultural, critical, and theoretical studies.